STRATEGI SOSIALISASI MIGRASI SISTEM PENYIARAN ANALOG KE DIGITAL DI JAWA TENGAH - Mubarok Mubarok; Made Dwi Adnjani (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2018)
This research describes the development, analyzing the communications strategy of socialization migration of tv analog to digital in Central Java using descriptive qualitative method. Data collection is done by interviewing 200 informants in four areas namely Semarang, Magelang, Purwokerto, and Pekalongan. Data analysis was undertaken by using analysis phase of strategic communication which includes formative research, strategy, research, and evaluation tactic. The results show a majority of residents Central Java did not know about migration plan of analog to digital tv. It is a challenge to plan a proper communications strategy according to conditions in Central Java so that the migration can run well and make benefit for all parties. Certainty roadmap migrations will ease the preparation of the communications strategy. The contribution of this research is to provide communication strategy of socialization of digital broadcast system in Central Java.